A Mixed-Methods Study on Advancing Critical Listening in English Language Teaching: Project-Based Interview Tasks in the Uzbek Undergraduate Context - Khodjakulova, Nargiza; Samatova, Barnokhon; Khodjakulova, Nodira (Forum for Linguistic Studies, 2025)
This study examines the effectiveness of interview-based project learning in developing critical listening skills among undergraduate EFL students at universities in Uzbekistan. Although such skills are crucial for academic achievement and communication, they are often neglected due to traditional approaches emphasizing repetition and bottom-up comprehension while overlooking higher-order analytical and reflective listening processes. To address this gap, the study implemented a three-stage instructional model built around structured interview tasks: (1) analysis of authentic interviews, (2) student designed and conducted interviews, and (3) peer evaluations using rubrics focused on critical listening indicators. The research was conducted with 120 philology students across four universities and employed a mixed-methods design. Quantitative data were collected through pre- and post-tests measuring inference, analysis, and evaluative sub-skills, while qualitative insights were obtained from semi-structured interviews and classroom observations. Three research questions guided the study: the impact of interview-based projects on critical listening sub-skills, the contribution of structured tasks to reflective and analytical listening, and student and teacher perceptions of the approach. Findings indicated significant gains in learners’ ability to critically analyze spoken input and make evidence-based judgments. Both students and teachers expressed positive views of the model, emphasizing its effectiveness and relevance to contemporary EFL contexts. The results highlight the pedagogical value of integrating project-based and communicative approaches in language teaching. Structured interview tasks not only foster critical listening but also enhance digital competencies, offering a strong alternative to conventional listening practices in Uzbekistan’s higher education system.